The Role of Village Government in Improving the Welfare of Micro and Small Business Actors in the Digital Era - Indarwati Rahman; Febri Hariyanto; Perayanti Perayanti; Umi Azizah; Ripela Ripela; Rola Pola Anto (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The Bendewuta Village Government has the responsibility and role as a motivator, facilitator and guide as well as a policy maker to encourage the welfare of village communities, especially Micro, Small and Medium Enterprises (MSMEs), considering that MSME income in the digital era is not yet optimal. Objectives: The purpose of this research is to reveal and analyze the role of village government in encouraging the improvement of the welfare of Micro and Small Business actors in the Digital era in Bendewuta Village, Wongeduku District. Methods: This study uses a qualitative descriptive method as a scientific approach that can be used to reveal the facts about the role of village government in encouraging increased welfare of MSME actors in Bendewuta Village in the digital era. Results: The results of this research indicate that the role of village government in encouraging the improvement of the welfare of MSMEs is as a motivator, facilitator, mentor, companion, village policy maker, village program implementer, village development coach, and person responsible for village community welfare. Through this role, micro, small, and medium enterprises can obtain information about business development in the digital era both from the village government and collaboration with universities that provide counseling on how to increase income and welfare for MSMEs in Bendewuta Village. Conclusion: The findings highlight the need for region-specific strategies and the optimization of inclusive socio-economic development programs to sustainably reduce poverty in Southeast Sulawesi.